(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Terricolous lichen communities of Plain part of Crimena Peninsula (Ukraine) form five associations, from them four we described first here: Enchylietum tenaxis Khodosovtsev ass. nov., Placidiopsietum cinerascentis Khodosovtsev ass. nov., Seirophoretum lacunosae Khodosovtsev ass. nov., Cladonietum endiviaefoliae Th. Müller (1951) and Circinarietum fruticulosae Khodosovtsev ass. nov. Associations belong to the two unions Toninion coeruleonigricantis Hadač (1948) and Sphaerothallio-Xanthoparmelion vagantis Crespo et Barreno (1978) from class Psoretea decipientis Mattick (1951). We showed ecological peculiarities and directions of successions in lichen associations of Plain Crimea. Six phytocoenotic tables are given in this paper.